An investigation into SOP based contract dispute adjudication process - Li, YanLing. (2013)
Security of Payment Act was first introduced in Singapore under the Building and Construction industry. This Security of payment Act officially started its operation on 1st April 2005. Singapore is the 7th country to adopt this regime after countries including United Kingdom, Australia (News South Wales, Queensland, Victoria and Western Australia) and New Zealand. It is evident that the implementation of this Adjudication regime has largely benefitted those who are legally bonded in the construction contract. The sufficient time given for the start, up to the end of the adjudication determination has helped in resolving the disputes efficiently between the Claimants and Respondents. However, there are still many Claimants and Respondents who failed to follow the stringent timeline closely, resulting in putting themselves in a disadvantage position under the Adjudication. The most common problems are the inability to file Adjudication Responses within 7 days. Adjudication Application was submitted at the wrong timing, Payment Claims served at the wrong timing and failure to serve the Payment Response. Therefore, four case studies were selected to identify the common issues in the new adjudication regime implemented. In the report, the issues will be analysed and understand on why the user will make the same mistakes. Through the understanding of the user’s common problem, more guidance information will be added in the checklist. Ultimately, the making of the new checklist hopes to rectify the common problems and achieve greater effective use of the SOP Act.